The Relationship between Risk Perception and Stress towards Exercise Behavior of Pregnant Women with Gestational Diabetes Mellitus: Walailak Suwanpakdee - Suwanpakdee, Walailak; Buddam, Maliwan; Lahukarn, Benjawan (Princess of Naradhiwas University Journal, 2024)
The purpose of this correlational descriptive study was to examine the relationship between risk perception and stress towards exercise behavior of pregnant women with gestational diabetes mellitus. Samples were 90 pregnant women with type A1 gestational diabetes who met the eligible criteria and received antenatal care at Maharaj Hospital in Nakhon Si Thammarat from March to October 2023. Instruments used for data collection were personal data questionnaire, the risk perception assessment during pregnancy, the stress measurement, and exercise behavior questionnaire. Alpha’s Cronbach coefficient reliability index values were.94,.91, and.80, respectively. Data analysis used descriptive statistics and the Pearson correlation coefficient. The following were the findings: The average risk perception during pregnancy score was moderate (M = 305.42, SD = 154.75). The average stress score was moderate (M = 40.78, SD = 9.22), and the average exercise behavior score was moderate (M = 34.41, SD = 8.30) There was a statistically significant positive correlation between risk perception and stress (r =.260, P <.05). Risk perception had statistically substantially positive correlation with exercise behavior (r = .240, P < .05), while there was no statistically significant correlation between stress and exercise behavior. These findings can be used by healthcare professionals to assist pregnant women with gestational diabetes mellitus perceive their risks, modify their exercise behavior, and improve their ability to control blood glucose levels.